Rút trích ngữ liệu song song từ ngữ liệu không thật sự song song Anh Việt - Trần, Ngô Như Khánh (Trường Đại học Đà Lạt, 2012)
In this paper, we present a method to extract parallel sentences from English-Vietnamese comparable (non-parallel) corpus. By using the result of automatic word alignment between sentences. We build a parallel sentences classifier based on Maximum Entropy model.